Agostinho Neto: Pure Poetic Discourse and Mobilization Rhetoric - Janis L. Pallister (Studies in 20th & 21st Century Literature, 1991)
Neto's importance in relationship to the modern genre we will call militant or guerilla poetry and his considerable poetic gifts as well call for a mainstreaming of his literary contributions. "Protest poetry" might more aptly describe his oeuvre; the term is certainly a somewhat better representation of his content than "guerilla poetry" or "poetry of combat." But whatever word is used to sum up that content, in the article on Neto one sees contextually how this talented poet fuses his ideologies with his structures, and intertextually how he avoids the diatribes, the invective and the stereotypically strident rhetoric of most guerilla poetry in a way scarcely imitated by his poetic "counterparts." Selected details of his biography are also highlighted as they bear upon his poetry; e.g. his physician's regard which is at stake in certain passages of "Kinaxixi" and "Um aniversário."
Keywords: Agostinho Neto; modern genre; militant poetry; guerilla poetry; Protest poetry; oeuvre; poetry of combat; ideologies; structures; intertextually; diatribe; counterparts; Kinaxixi; Um aniversário